Islamic Financial Characteristics and the Sustainability of Islamic Banking in Indonesia: Challenges and Opportunities - Yusuf, Sri Dewi; Mokoagow, Muhamad; Nur, Muhammad; Rauf, Spandi (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This research aims to examine the implementation of Islamic finance in Islamic banking in Indonesia based on the characteristics of Islamic finance, namely Tauhid (Monotheism), Adl (Justice), Nubuwwah (Prophethood), Khilafah (Stewardship), and Ma’ad (Afterlife). This study also aims to serve as a means for the Indonesian public to obtain information related to the application of financial systems in Islamic banking. The researcher employs a qualitative research method, using secondary data sourced from literature, including journals, articles, documentation, written texts, and relevant materials related to the research topic. The results of this study indicate that Islamic banks indeed practice their activities in accordance with Sharia regulations. The five values or characteristics of Islamic finance serve as the main foundation in its implementation. Firstly, in the concept of Tauhid, leaders consistently maintain their devotion to Allah. Moreover, Islamic banks make all policy decisions based on the Qur'an and Sunnah (traditions of the Prophet). Secondly, in terms of Adl, this principle is evident in the implementation of Islamic banking contracts, which do not prioritize personal gain in their collaborations. Thirdly, the principle of Nubuwwah, which prohibits monopolies and encourages cooperation in community building, aligns with one of the practices of the Prophet Muhammad during his time. Fourthly, Khilafah, through the practice of Islamic banking involving zakat contributions from its activities, demonstrates that Islamic banks in Indonesia do not forget their obligation to contribute to a just economy. Lastly, Ma’ad; Islamic banks always consider the ultimate outcome of their activities, as everything they undertake will be rewarded or punished in accordance with their deeds.